(untitled) - ANWAR ALALANDA, MANZAR AHMED (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Fast Food restaurants are practice certain marketing strategies recently by targeting children with creative ideas of products for their profit rather than consider the implications on child's health. This study will compare between McDonald's and Burgers King, because they the popular brands have received the consent of the child, and have been made clear efforts which competed in the development of their meal and their toys which provided happiness to the child. A questionnaire survey and statistical analysis is conducted to identify the characteristics of brand loyalty that effect from children and their parents as well as analyse the performance of fast food joints in Jeddah, Saudi Arabia. The findings indicated that the children do not rely on taste as one factor but there are separate factors that affect their choice when one seeks information regarding brand loyalty of fast food joints.